Integrative Gastroenterology. - Mullin, Gerard (Oxford University Press, USA, 2011)
This volume, under the authorship of Gerard Mullin at Johns Hopkins, and under the series editorship of Andrew Weil, the leading authority on integrative medicine in the US, offers a critical appraisal of integrative approaches to gastrointestinal disorders, including discussions of what's known and what's not known, and making practical recommendations on advising patients on controversial areas. In managing the patient, alternative therapies are never to be seen as substitutes for mainstream medical care, but always 'integrated' into the overall regimen, and always subjected to the best avai.